Technology's Refuge The use of technology by asylum seekers and refugees - Leung, Linda (UTS Shopfront Series, 2009)
An investigation into the use of information communication technologies by refugees during flight, displacement and in settlement, this book examines the impact of Australia's official policy of mandatory detention on how asylum seekers and refugees maintain links to diasporas and networks of support. Given the restricted contact with the world outside of the immigration detention centre, the book juxtaposes forms and processes of technology-mediated communication between institutionalised detention, with those of displacement and settlement. It finds that while there are obstacles to communication in situations of conflict and dislocation, asylum seekers and refugees are able to 'make do' with the technology options available to them in ways which were less constrained than in detention settings. The book also outlines how communication practices during the settlement process focus on learning new technologies, and repairing the disconnections with family members resulting from separation and detention.